Electromyographic examination of knee training using a hybrid assistive limb after anterior cruciate ligament reconstruction: A case report - Yuichiro Soma; Hirotaka Mutsuzaki; Tomokazu Yoshioka; Shigeki Kubota; Yukiyo Shimizu; Akihiro Kanamori; Masashi Yamazaki (Elsevier, 2022)
Muscle co-contraction can result in higher joint contact forces, compromising knee joint mobility for stability, thus leading to impaired lower extremity neuromuscular control, delayed return to sports, and increased incidence of secondary anterior cruciate ligament (ACL) injury post-ACL reconstruction. Hybrid assistive limb (HAL) training has the potential to correct impairment of antagonistic or synergistic muscle movement of the knee joint through bioelectric signal feedback from muscle signals with computer processing. We considered that HAL training would contribute to improve peak muscle torque through coordinating or decreasing higher levels of muscle co-contractions and reducing differences between hamstring and quadriceps muscle activity on electromyography (EMG). While playing handball, a 20-year-old female injured her ACL upon landing on one leg. Two months post-injury, she underwent arthroscopic, anatomic single-bundle ACL reconstruction with a semitendinosus tendon autograft. At a 4-month follow-up, she underwent knee HAL training, which was performed once a week for three sessions. EMG data were collected during the evaluations of pre- and post-HAL training. The average muscle amplitude was used to calculate the difference between vastus lateralis (VL) and semitendinosus (ST) muscles, and the muscle co-contraction index (CCI). The CCI reflects the simultaneous activation of antagonistic muscles, which is determined for knee extensor-flexor muscle pairs. Post-knee HAL training, the CCI of the lateral hamstring and quadriceps muscles during extension was lower than that during pre-HAL training in all sessions. However, no differences were found in the CCI for the medial hamstring and quadriceps muscles during extension and flexion pre- and post-knee HAL training. For post-knee HAL training, the difference between VL and ST EMG data during a closed-chain squat was lower than that during pre-HAL training in all sessions. Knee HAL training contributed to improved peak muscle torque through coordinating or decreasing higher levels of muscle co-contractions, and it reduced differences between hamstring and quadriceps muscle activity in the ACL reconstructed leg as depicted by EMG.